2016
DOI: 10.1002/ange.201512038
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coordination of Black Phosphorus for Robust Air and Water Stability

Abstract: At itanium sulfonate ligand is synthesized for surface coordination of black phosphorus (BP). In contrast to serious degradation observed from the bare BP,the BP after surface coordination exhibits excellent stability during dispersion in water and exposure to air for al ong period of time, therebys ignificantly extending the lifetime and spurring broader application of BP.Atomically thin black phosphorus (BP), an ew member of two-dimensional (2D) materials,h as attracted increasing interest because of its uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 54 publications
4
138
0
1
Order By: Relevance
“…S6), and further modification is required to enhance the stability. 29 Extinction spectra are acquired from the BP@Au composites. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6), and further modification is required to enhance the stability. 29 Extinction spectra are acquired from the BP@Au composites. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 BP has strong in-plane bonds in conjunction with weak van der Waals interlayer interactions thereby enabling exfoliation into few-layer BP sheets or phosphorene (single-layer BP). [20][21][22][23][24] Since 2014, BP has attracted tremendous research interest [25][26][27][28][29][30][31][32][33][34][35][36][37][38] because of its unique properties such as layerdependent direct bandgap, 28,39 anisotropy, 25,26,31,32,34,40 hingelike structure, 41 and quasi-one-dimensional excitonicnature, 42 all of which contrast markedly with those of other types of 2D materials. Nevertheless, BP degrades under ambient conditions as a result of the reaction with oxygen (P→P x O y ) and subsequent transformation to PO 4 3-in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to free ZNS, this prolonged effective drug duration of released ZNS may provide better neuroprotective effects in vivo. 25,47,48 Neuron and axon density are critical indicators of anatomical recovery from SCI. 43,49 In histopathologic examination, a statistically significant increase of NF was observed in the ZNS-M group (Figure 9).…”
Section: Zns-m Groupsmentioning
confidence: 99%
“…Although BP bulk stands out as the most thermodynamically stable allotrope of phosphorus, the atomically thin phosphorene gradually degrades in the presence of air . It is found that unprotected phosphorene possesses strong affinity for oxygen or water molecules upon exposure to ambient conditions, which presents a fundamental obstacle hindering the potential adoption of phosphorene in (photo) electronics and electrochemical devices.…”
Section: Air Instability Of Phosphorene and Passivation Approachesmentioning
confidence: 99%